Probiotic Bacillus subtilis Protects against α-Synuclein Aggregation in C. elegans - Goya, María Eugenia (2020)
How the gut microbiome affects Parkinson's disease remains unclear. Goya et al. show that the probiotic B. subtilis strain PXN21 inhibits and clears α-synuclein aggregation in a C. elegans model. The bacterium acts via metabolites and biofilm formation to activate protective pathways in the host, including DAF-16/FOXO and sphingolipid metabolism.